The power of time: old age and old men in ancient Greek drama - Polyakov, M (2013)
The study of old age in the humanities has developed significantly in the last few decades, but there is still much scope for progress. This thesis, therefore, seeks to contribute to the growing academic discourse in this area by considering ageing as it is represented in ancient Greek theatre. At the same time, it seeks to take its place within Classical Studies by developing new readings of the plays. To develop a context for its analysis, this study begins with consideration of the contemporary demographics, social position, and stage portrayal of old age, and following this dedicates a chapter to each of the four surviving fifth century dramatists. In Aiskhylos’ Agamemnon, old age emerges as a crucial element in choral self-identity, and an important component of the authority that they display. Following this, the thesis considers the chorus of Euripides’ Herakles, in particular its use of metadramatic language, and the impact this has on plot-development and the representation of their age. The next chapter, on Oidipous Koloneus, shifts to consideration of the protagonist. The old age of Oidipous emerges as a powerful driver of his mental and spiritual power, and forms a striking background to the exploration of his character. The final chapter of the thesis examines how mechanisms of renewal that old men undergo in Aristophanes’ comedies (Knights, Akharnians, Peace, Wasps, Birds) differ across the dramas, and the impact this difference has on their interpretations. Such reassessments of ancient dramatic texts through the lens of old age can provide significant insight into the complexity of old men’s characterisations and of their involvement in the dramas. At the same time (from a gerontological perspective), this thesis’ analysis contributes to the developing discussion of the history of ageing, and highlights the differences between the ancient and modern worlds in this respect.